(untitled) - Rezende, Lisa. (New York, 2006)
This is a helpful reference tool for students looking for basic information about specific scientific events. The entries inspire the reader to investigate the topic further. After reading sections of the book, the reader will have gained accurate information about scientific history, as well as a sense of how scientific discoveries build upon events of the past, and an understanding of the way scientific theories have changed over time.
Keywords: Science,Scientists,Khoa học niên đại; Chronology.,Biography